The Health and Demographic Surveillance System (HDSS) in Nouna, Burkina Faso, 1993-2007 - Sié, Ali; Louis, Valérie R.; Gbangou, Adjima; Müller, Olaf; Niamba, Louis; Stieglbauer, Gabriele; Yé, Maurice; Kouyaté, Bocar; Sauerborn, Rainer; Becher, Heiko (Global health action, 2010)
The Nouna Health and Demographic Surveillance System (HDSS) is located in rural Burkina Faso and has existed since 1992. Currently, it has about 78,000 inhabitants. It is a member of the International Network for the Demographic Evaluation of Populations and Their Health in Developing Countries (INDEPTH), a global network of members who conducts longitudinal health and demographic evaluation of populations in low- and middle-income countries. The health facilities consist of one hospital and 13 basic health centres (locally known as CSPS). The Nouna HDSS has been used as a sampling frame for numerous studies in the fields of clinical research, epidemiology, health economics, and health systems research. In this paper we review some of the main findings, and we describe the effects that almost 20 years of health research activities have shown in the population in general and in terms of the perception, economic implications, and other indicators. Longitudinal data analyses show that childhood, as well as overall mortality, has significantly decreased over the observation period 1993-2007. The under-five mortality rate dropped from about 40 per 1,000 person-years in the mid-1990s to below 30 per 1,000 in 2007. Further efforts are needed to meet goal four of the Millennium Development Goals, which is to reduce the under-five mortality rate by two-thirds between 1990 and 2015.